A Prospective Controlled Trial of the Optimal Volume for Neonatal Blood Cultures. Issue 4 (April 2015) - Yaacobi, Nurit; Bar-Meir, Maskit; Shchors, Irina; Bromiker, Ruben
Abstract : Background: Bacteremia is a frequent complication in neonatal intensive care units. Blood cultures are the standard for the diagnosis. It is a common practice to draw small blood volumes for culture from neonates in order to prevent anemia; however, this might compromise the test sensitivity. We examined whether using 1 mL of blood in a single aerobic bottle would improve the culture yield compared with our current practice of obtaining 2 samples of 0.5 mL of blood (aerobic and anaerobic bottles). Methods: A prospective controlled study was conducted between December 2009 and September 2010 at the neonatal intensive care unit of Shaare Zedek Medical Center, Jerusalem, Israel. Study population included newborns from whom blood cultures were obtained. A sample of 2 mL of blood from each patient was divided into a single aerobic bottle (1 mL; study sample) and into 2 aerobic and anaerobic bottles (0.5 mL each; control samples). Culture bottles were weighed before and after blood inoculation and time to positivity (TTP) was recorded. Results: We obtained 706 complete culture sets from 519 patients. Pathogens grew in 72 (10.2%) cultures from 37 patients. Isolation of organisms was significantly higher in the 0.5 mL control group (94.4% vs. 77.7%, P = 0.012). The TTP was similar in 0.5 mL and 1 mL aerobic bottles, but significantly longer in the anaerobic bottle. Conclusions: Allocating 1 mL of blood into 2 bottles, aerobic and anaerobic, improved the yield of the culture compared with 1 mL in a single aerobic bottle.